Assessment of water quality variation in rivers through comparative index technique and its reliability for decision making - Kitalika, Aldo; Machunda, Revocatus; Komakech, Hans; Njau, Karoli N (Tanzania Journal of Science, 2021)
The National Sanitation Foundation (NSF) and Weighed Arithmetic Index (WAI) methods for water quality index (WQI) have been studied to evaluate their reliability in water quality assessment in rivers. Water samples were collected in various GPS predetermined points in Temi, Nduruma, Tengeru and Maji ya Chai rivers-Tanzania during wet and dry seasons and were analyzed for several water quality parameters using standard methods as per APHA. Medium to excellent water qualities were observed for pristine environment in three rivers except Maji ya Chai under NSF and WIA methods, respectively. Excellent water quality was observed in the pristine environment of Temi and Tengeru rivers during wet season. Maji ya Chai water was identified unsuitable for drinking throughout the year. Fecal Coliforms (FC), Nutrients content, BOD and Fluorides (F-) were the major contributors to the poor water quality in Maji ya Chai whereas FC and Nutrients were a serious problem in flood-plain for other rivers. The two methods showed different overall Water Quality Indices using the same data thus, making them unreliable tools for water quality assessment when used simultaneously for the same purpose. Therefore selection of the method for water quality assessment and decision making may depend on the water use.